Researches on al-Farabi’s legacy in the Islamic Republic of Iran (Journal of Oriental Studies, 2020)
In connection with the 1150th anniversary of the great scientist Abu Nasr al-Farabi, recognized as the second teacher after Aristotle, the UNESCO declared the 2020 as the year of al-Farabi. The researches and cultural activities, which were carried out in different parts of the world about his life and works show the significant relevance of al-Farabi’s influence on human civilization to the present day. Al-Farabi, who left such an indelible mark in all fields of science a was recognized by Western scientists as a disciple of Plato and Aristotle, a person who paved the bridge between Western and Eastern civilizations; Eastern scholars consider him as the founder of Islamic philosophy and one of the most important representatives of the Turkic-Islamic civilization. The Kazakh people greatly respect al-Farabi, their great-grandfather, as one of the outstanding representatives of the Turkics of Central Asia and born in the Kazakh steppes, and consider it their duty to preserve, study and popularize his legacy of the entire world civilization. Therefore, we consider it important to collect data on ongoing researches in different countries and to be able to systematize and analyze them. Therefore, in this article, by using methods of collecting, sorting, differentiating and analyzing data in the Persian language, we will try to consider the scientific works and activities carried out in the Islamic Republic of Iran on study of the biography, works of the philosopher, the concepts of researches and in general show the role of al-Farabi in Iran. Key words: researches on al-Farabi, Islamic Republic of Iran, Farabi Studies.